Ontogeny of food grasping in mouse lemurs: behavior, morphology and performance. (3rd February 2019) - Boulinguez‐Ambroise, G.; Zablocki‐Thomas, P.; Aujard, F.; Herrel, A.; Pouydebat, E.
Abstract: In primates, grasping constitutes a vital function involved in many behaviors. Anatomical specializations of the prehensile extremities originated early‐on in their evolution. However, the precise functional and ecological contexts that have driven this evolution remain unclear. Interspecific comparative studies show that a given morphology can induce different grasping behaviors and also that a given behavior can be performed using different morphological structures. In this context, an intraspecific ontogenetic approach offers the opportunity to describe the relations between patterns in grasping behavior and patterns of grasping morphology. We quantified manual grasping strategies and the associated morphometric (i.e. segments lengths) and performance (i.e. pull strength) traits for both limbs during the development of a small arboreal primate, the gray mouse lemur ( Microcebus murinus ). Our results show an early onset of grasping in young mouse lemurs. Moreover, younger individuals had relative longer hindlimbs (i.e. tibia and metatarsus) allowing them to have near‐maximal levels of grasping strength. This very fast development despite an incomplete neuromuscular development highlights the importance of this grasping function directly after birth. Abstract : Anatomical specializations of the primates' prehensile extremities originated early‐on in their evolution. However, the precise functional and ecological contexts that have driven this evolution remain unclear. In this context, an intraspecific ontogenetic approach offers the opportunity to describe the relations between patterns in grasping behavior and grasping morphology. We quantified manual grasping strategies and the associated morphometric and performance traits for both limbs during the development of a small arboreal primate, the gray mouse lemur ( Microcebus murinus ). Our results show an early onset of grasping in young mouse lemurs. Moreover, younger individuals had relatively longer hindlimbs allowing them to have near‐maximal levels of grasping strength. This very fast development despite an incomplete neuromuscular development highlights the importance of this grasping function directly after birth.